A case of "voluntary nystagmus" and head tremor. Issue 12 (December 1993) - Lee, J; Gresty, M
Abstract : A 24-year-old woman presented with nystagmus and head tremor. Both were transient and could be executed simultaneously at different frequencies of oscillation. It is unusual for these two movements, which can be voluntary, to occur together. Suspicions of an acquired disease were not confirmed on further investigation using DC-coupled electro-oculography and angular accelerometry, and on an admission by the patient that the nystagmus could be voluntary. Voluntary nystagmus can become semi-automatic and a patient may be able to simulate more than one "involuntary movement" simultaneously yet at different frequencies.